USING MYSTERY PHOTO ON STUDENTSâ VOCABULARY ACHIEVEMENT - Rusli, Tri Indah; ayu, Aulia Suminar (Metacommunication: Journal of Communication Studies, 2018)
ABSTRACTÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â  This study aims to find out whether there is or not a significant effect of using Mystery photo in improving studentsâ vocabulary achievement at the VII A grade of SMP Negeri 2 Oheo. The research question in this study âis there any significant effect of studentsâ vocabulary achievement after being taught through Mystery photo at the VII A grade of SMP Negeri 2 Oheo?â This study used quasi experimental design. The sample of this research was 60 students which divided into two classes. In collecting the data, the researcher used vocabulary test which consists of multiple-choice, fill in the blank and matching test. In conducting this study, the researcher taught experimental class by using Mystery photo without a control class. The result of this study showed that the teaching of vocabulary by using Mystery photo could improve the studentsâ vocabulary achievement at the VII grade of SMP Negeri 2 Oheo. It can be proved that the analysis of tcount 5.745 was higher than ttable 1.671 after consulting the ttable at the significant level 0.05 and the degree of freedom 58. Ho was rejected and H1 was accepted.Keywords: Â mystery photo, vocabulary achievement, studentsâ improvement